Combined therapy of human amnion-derived mesenchymal stem cells and scalp acupuncture alleviates brain damage in a rat model of cerebral palsy - Yu Zhou; Xu-Huan Li; Lu-Na He; Li-Na Wang; Jing Zang; Dong-Ming Wang; Jing Gao; Xue-feng Yu (IBRO Neuroscience Reports)
Background: Cerebral palsy (CP) is a prevalent cause of physical disability in children, often resulting from hypoxic-ischemic encephalopathy, with current therapies often failing to address the underlying pathophysiology. This study aimed to investigate the potential synergistic effects of human amnion-derived mesenchymal stem cells (hAMSCs) combined with scalp acupuncture in a rat model of CP. Methods: Twenty male Sprague-Dawley rats were randomly divided into four groups: Sham, CP, hAMSCs, and hAMSCs+scalp acupuncture (hAMSCs+AP). The CP model was induced via left common carotid artery ligation. hAMSCs were administered through tail vein injection, followed by scalp acupuncture at Baihui (GV20) and Qubin (GB7) points. Neurobehavioral function was assessed using the Bederson score, and brain tissues were analyzed using hematoxylin and eosin (H&E) staining, TUNEL staining, and RT-qPCR for apoptosis-related genes. Results: The CP group exhibited significant neurobehavioral deficits and increased apoptosis. Both hAMSCs and hAMSCs+AP treatments improved neurobehavioral function and reduced apoptosis. The combination therapy further decreased apoptosis levels, normalized mRNA expression of Bax, Caspase 9, and Caspase 3, and alleviated histological damage. Conclusions: The combination of hAMSCs and scalp acupuncture provides a promising treatment for CP, potentially alleviating brain damage through apoptosis regulation. Further studies are required to elucidate the detailed mechanisms and assess clinical feasibility and safety.